Inequalities of the Type Hermite–Hadamard–Jensen–Mercer for Strong Convexity. (1st November 2021) - Adil Khan, Muhammad; Anwar, Saeed; Khalid, Sadia; Sayed, Zaid Mohammed Mohammed Mahdi
Abstract : By using the Jensen–Mercer inequality for strongly convex functions, we present Hermite–Hadamard–Mercer inequality for strongly convex functions. Furthermore, we also present some new Hermite‐Hadamard‐Mercer-type inequalities for differentiable functions whose derivatives in absolute value are convex.